Kepemimpinan dan Komunikasi serta Keterampilan Manajerial Pendidikan - Rima Erviana; Istikhori Istikhori; Rubi Babullah; Nazrul Zimatul Rizky; Siti Nurafifah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This research explores the relationship between leadership, communication, and managerial skills in an educational context. The main focus is how effective leadership and good communication can improve managerial skills in an educational environment. The research results show that participative leadership and open communication contribute significantly to improving managerial skills, including strategic planning, decision making, and resource management. These findings emphasize the importance of leadership and communication training in managerial development in the education sector, which can ultimately improve the performance and effectiveness of educational institutions.